2016
DOI: 10.1007/s00167-016-4254-3
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of bony resection from patient-specific guides during total knee arthroplasty

Abstract: IV, case series with no comparison group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 22 publications
(55 reference statements)
1
18
0
Order By: Relevance
“…Instead of technology, KA surgeons rely on the caliper to detect a resection deviation from the femoral target. Correcting a distal over-resection is achieved by modifying chamfer cuts and filling any gaps with cement [ 4 , 5 ]. In contrast, correcting a posterior over-resection is more challenging, which some surgeons left under-corrected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead of technology, KA surgeons rely on the caliper to detect a resection deviation from the femoral target. Correcting a distal over-resection is achieved by modifying chamfer cuts and filling any gaps with cement [ 4 , 5 ]. In contrast, correcting a posterior over-resection is more challenging, which some surgeons left under-corrected.…”
Section: Discussionmentioning
confidence: 99%
“…Technology proponents argue that robotic, navigation, and patient-specific instrumentation more accurately hit the femoral target than manual instruments [ 12 , 14 , 22 , 28 ]. Whereas manual instrument proponents argue that technology lengthens the operation, adds expense, and induces stacked errors arising from transforming images into a 3D model, planning the resection planes, and registering instruments [ 1 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies on the accuracy of osteotomy provided by patient-specific cutting guides in TKA, the acceptable difference between planned and actual bone cuts has been reported as 1.5 mm or less [ 12 ]. The difference between the planned and actual thickness of resected bone for osteotomy has been reported to range between 0.5 and 2 mm when using patient-specific 3D cutting guides [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the planned and actual thickness of resected bone for osteotomy has been reported to range between 0.5 and 2 mm when using patient-specific 3D cutting guides [ 13 , 14 ]. In an 81-knee series, Levy et al [ 12 ] showed that this difference was within acceptable limits for about 80% of femur cuts and 70% of tibial cuts, indicating that patient-specific cutting guide has only moderate accuracy. Kievit et al [ 14 ] studied the accuracy of osteotomy when patient-specific instrumentation was used for TKA in cadavers and found high similarity between planned and actual osteotomy planes.…”
Section: Discussionmentioning
confidence: 99%